2022
DOI: 10.1108/jaee-09-2021-0294
|View full text |Cite
|
Sign up to set email alerts
|

Profit, cash flow, and leverage: the case of ASEAN stock market performance during the COVID-19 pandemic

Abstract: PurposeThe coronavirus disease 2019 (COVID-19) outbreak in the first quarter of 2020 has caused a severe decline in stock markets worldwide. While prior studies in developed markets found that workplace closure can negatively impact the capital market (e.g. Ozili and Arun, 2020), lesser is known about how it impacts emerging capital markets, which may have different characteristics and behaviour (Harjoto et al., 2021). Hence, this study seeks to uncover stock performance around workplace closure dates of firms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Adequate cash flows may boost the share prices of listed EEP companies. Some studies have shown that holding excess cash can increase the value of a business when it is operating in an uncertain environment and when it has high growth opportunities and low debt levels [32,33].…”
Section: Literature Review and Research Frameworkmentioning
confidence: 99%
“…Adequate cash flows may boost the share prices of listed EEP companies. Some studies have shown that holding excess cash can increase the value of a business when it is operating in an uncertain environment and when it has high growth opportunities and low debt levels [32,33].…”
Section: Literature Review and Research Frameworkmentioning
confidence: 99%
“…by Dwiyani Sudaryanti, Mohamad Bastomi herding behavior, particularly during the pandemic. Abbas & Nainggolan (2022) contributed to this discourse by revealing a positive association between cumulative abnormal returns (CARs) around workplace closure dates and current ratios, while observing an inverse relationship with long-term debt ratios.…”
Section: Introductionmentioning
confidence: 99%